Financial Ratios on the Bankruptcy Rates with Profitability as Moderating Variables on JII70 - Yuliawati, Yuliawati; Umaroh, Rodiah (AIBPM Publisher, 2022)
The purpose of this study was to determine the level of corporate bankruptcy and the effect of CR and DAR on bankruptcy rate with EPS as a moderating variable. The object of this research is the companies listed on the Jakarta Islamic Index 70 (JII70) for the period May 2018 to May 2021. The sampling technique using purposive sampling obtained 23 companies used as samples in the study. The analysis technique uses panel data regression and residual data with Moderated Regression Analysis (MRA). From the results of the study, it is known that the majority of companies that were members of JII70 for twelve years 2010-2021 were in a healthy condition. There were at least 13 healthy companies during the study period from a total sample of 23 companies. For companies that fall into the category of healthy and gray area, there are 6 companies, and 4 companies are in a healthy condition, gray area, and bankrupt. While there are no companies that are in a gray area and go bankrupt condition. The results of panel data regression and MRA show that CR and DAR together have a significant effect on the level of bankruptcy. Partially, CR has a significant positive effect while DAR has a significant negative effect on the level of corporate bankruptcy. Keywords: CR, DAR, EPS, and Bankruptcy Rate